Emphasis of the dialogue between Christians and Marxists in Slovenia in the 1980s - Zalta, Anja (Poligrafi, 2020)
The paper presents (some) highlights of the dialogue between so-called Marxists and Catholics in the 1980s in Slovenia. The central axis of the debate revolves around (understanding) the method of historical materialism and emphasizing Marxism as a worldview. The paper focuses on theological responses to historical materialism on the basis of presentations of the historical background, especially the attitude of the Church and papal positions towards socialism and consequently towards Marxism and communism, as well as the issue of re-Catholicization. Proceeding from the context of anti-communist restoration, the rhetoric of the “cultural struggle” as a conflict between two worldviews remains particularly problematic, which consequently brings and consolidates the idea that Marxism and (Catholic) religiosity are in a kind of a conflict. The article problematizes such positions, and at the same time shows the importance of the introduction of historical materialism as a method adopted (to some extent) by the socialist theology of the Auxiliary Bishop of Maribor Vekoslav Grmič and his circle.